HARMONICS ELIMINATION USING FILTER DESIGN (International Journal of Engineering and Computer Science, 2013)
The aim of this paper is to establish an analytical method for the design of the Improved low pass Broadband Passive harmonic Filter (IBF) that absorbs current harmonics caused by three phase bridge rectifiers used in motor drives. The design attempts to comply with the IEEE Standard 519-1992 recommended harmonic limits applied to the current harmonic limits of three phase rectifier systems. In this paper an analytical design method of the improved broadband passive harmonic filter (IBF) for three phase diode rectifier front-end type adjustable speed drives is presented. The method is based on frequency domain modeling of the rectifier and filter. The success of the method involves accurate representation of the load harmonics. With the harmonics well defined, the harmonic and fundamental frequency equivalent circuits are utilized to analytically calculate the voltages/currents. Thus, the size and the performance of the filter can be optimized. The analytical method is verified via computer simulations and laboratory experiments. Also a performance comparison of various passive harmonic filters for three-phase diode rectifier front-end type adjustable speed drives is provided. The comparison involves the input current total harmonic distortion, input power factor, rectifier voltage regulation, energy efficiency, size, and cost. The parallel/series harmonic resonance problem related issues are addressed and unbalanced operation performance investigated. The comparison is based on analysis and computer simulations and the results are validated by laboratory experiments.